1994
DOI: 10.1016/0035-9203(94)90441-3
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis in the Republic of São Tomé and Principe: characterization of Schistosoma intercalatum

Abstract: This paper reports the morphological and biochemical characterization of the species of Schistosoma infecting humans in the Republic of São Tomé and Principe. The eggs are typical in shape and size of S. intercalatum, measuring on average between 174.5 microns and 189.1 microns. The eggs are voided in the faeces and not the urine of infected people. The parasite experimentally develops in several different species of Bulinus belonging to the B. forskalii group, including B. forskalii, with a minimum prepatent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Comparison of egg sizes found in the present study with published data shows that: (i) the mean egg length of the S. haematobium morphotype (146  μ m for Dangbo samples and 139  μ m for Doh samples) was similar to that of S. haematobium reported by Pitchford [23] (131–142  μ m), Loker [24] (144  μ m), and Richard-Lenoble and colleagues [25] (146  μ m); (ii) the mean egg length of the intermediate morphotype (151  μ m for both Dangbo and Doh samples) was similar to that of hybrids collected from urine by Mintsa Nguema and colleagues [26] (144 and 159  μ m) and Brown and colleagues [8] (151  μ m); (iii) the mean egg length of the S. guineensis morphotype (158  μ m for Dangbo samples and 164  μ m for Doh samples) was less than that of S. guineensis collected from feces by Wright and colleagues [6] (172  μ m), Richard-Lenoble and colleagues [25] (173  μ m), Southgate and colleagues [7] (175–189  μ m), and Pagès and Théron [27] (188  μ m). Consequently, our morphological data are correlated with previous data for S. haematobium and hybrids of S. haematobium and S. guineensis , but inconsistent with previous data for S. guineensis .…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of egg sizes found in the present study with published data shows that: (i) the mean egg length of the S. haematobium morphotype (146  μ m for Dangbo samples and 139  μ m for Doh samples) was similar to that of S. haematobium reported by Pitchford [23] (131–142  μ m), Loker [24] (144  μ m), and Richard-Lenoble and colleagues [25] (146  μ m); (ii) the mean egg length of the intermediate morphotype (151  μ m for both Dangbo and Doh samples) was similar to that of hybrids collected from urine by Mintsa Nguema and colleagues [26] (144 and 159  μ m) and Brown and colleagues [8] (151  μ m); (iii) the mean egg length of the S. guineensis morphotype (158  μ m for Dangbo samples and 164  μ m for Doh samples) was less than that of S. guineensis collected from feces by Wright and colleagues [6] (172  μ m), Richard-Lenoble and colleagues [25] (173  μ m), Southgate and colleagues [7] (175–189  μ m), and Pagès and Théron [27] (188  μ m). Consequently, our morphological data are correlated with previous data for S. haematobium and hybrids of S. haematobium and S. guineensis , but inconsistent with previous data for S. guineensis .…”
Section: Discussionmentioning
confidence: 99%
“…However, IPIs studies in SAC are quite rare; only two studies conducted in 1987 and 2005 indicated that the prevalence of A. lumbricoides, T. trichiura, and some intestinal protozoan infections were fairly high in SAC [13][14][15][16][17] . Largely from 2005 onwards, the DRSTP accepted the advice of non-governmental organizations (NGOs) to begin SAC-based deworming program using a single-dose mebendazole regimen annually.…”
Section: Introductionmentioning
confidence: 99%
“…Although limited information is available regarding the IPIs status among inhabitants of the Democratic Republic of Sao Tome and Principe (DRSTP) [13][14][15][16][17] , like other developing countries, IPIs are supposedly a major health problem in the DRSTP due to tropical climatic and poor hygienic conditions. However, IPIs studies in SAC are quite rare; only two studies conducted in 1987 and 2005 indicated that the prevalence of A. lumbricoides, T. trichiura, and some intestinal protozoan infections were fairly high in SAC [13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…The Zaire strain of S. intercalatum was known to occur only in the North East of Zaire while the Lower Guinea strain was reported in Gabon and Cameroon (Doumenge et al 1987). Over the last 10 years, new foci of transmission of the Lower Guinea strain have been reported, either within the historically endemic countries (Gabon and Cameroon) (Brown et al 1984;Burchard & Kern, 1985) or in new countries (Nigeria, Mali, Equatorial Guinea and Sao Tome) (Corachan et al 1987(Corachan et al , 1988Arene, Ukeibo & Nwawze, 1989;Simarro, Sima & Mia, 1989;Southgate et al 1994). Sporadic cases of S. intercalatum infections have also been reported from Central African Republic, Chad, Angola, Burkina Fasso, Congo, Uganda and Senegal, but no active foci of transmission have so far been described in these countries.…”
Section: Introductionmentioning
confidence: 99%